Improving Pronunciation and Speaking Confidence with Speechache in 8th Grade English Learning - Aulia Wahyu Khoirunnisa; Novia Trisanti (Language Circle: Journal of Language and Literature, 2025)
This study explores the challenges and benefits of transforming pronunciation teaching through technology integration, specifically focusing on the insights of English language teachers. Utilizing semi-structured interviews, the research examines educators' experiences with implementing tools like SpeechAce in their classrooms. Findings reveal that while teachers recognize the potential of technology to enhance student engagement and provide immediate feedback, they also encounter obstacles such as varying levels of student familiarity with technology and the need for adequate training. Teachers emphasized the importance of balancing traditional teaching methods with innovative approaches to effectively address pronunciation challenges. Overall, the study highlights the dual role of technology as both a facilitator of improved pronunciation skills and a source of pedagogical challenges, offering valuable recommendations for educators seeking to enhance their teaching practices in an increasingly digital learning environment.